EKSISTENSI HAK ULAYAT MASYAKAT HUKUM ADAT NGATA TORO - arto oktavianto arto (Jurisprudentie: Jurusan Ilmu Hukum Fakultas Syariah dan Hukum, 2020)
AbstractThis research is aimed to know both the existence of the indigenous people of Ngata Toro and the law protection. This research type is empirical research. The data is qualified as primary and secondary data. Primary data is obtained through interviews and secondary data is obtained through study of literature. The collected data is treated with a descriptive conclusion of qualitative analysis approach. The research result shows the regional right existence of the indigenous people in Sigi, Central Sulawesi which is still existing and running as normal according to the public applied rules. The law protection of indigenous people of Ngata Toro in a regency has not been suitable yet with the existent rule inasmuch as many of harm things happens to the indigenous people of Ngata Toro and there is no regional rule to protect the indigenous people’s rights. This research has become a reference to the local government to make regional rule of the indigenous people of Ngata Toro.